Faktor-Faktor yang Mempengaruhi Dinamika Kecukupan Pangan Rumah Tangga Petani Padi Sawah di Kota Gorontalo - L Lusiana; Asda Rauf; Ria Indriani (Fapetrik-UMPAR, 2021)
Gorontalo's paddy fields had decreased from 833 Ha in 2019 to 916 Ha in 2010. The decreased means there has been a reduction in the rice field area of around 83 Ha for nine years. Land conversion is one of the factors that farmers in Gorontalo City cannot avoid. The household food security of lowland rice farmers in Gorontalo City based on the food security score is in a food-insecure condition, 60.43%. This study aims to analyze the factors that influence the dynamics of staple food adequacy at the household level of lowland rice farmers in Gorontalo City. The research was carried out in the Gorontalo City area in July-September 2020. Primary data were sourced from lowland rice farmers in Gorontalo City, while secondary data was obtained from BPS, Food Service, and sub-district offices. The sampling technique was a simple random method with a total of 66 rice farmers. Data analysis to measure the model of factors that influence the dynamics of food sufficiency at the household level of rice farmers in Gorontalo City uses a linear probability model. The results showed that the factors influencing the dynamics of staple food adequacy at the household level of lowland rice farmers in Gorontalo City are rice production, rice consumption, farmers' exchange rate (NTP), land area, and total household income. Meanwhile, education, age, and several dependents did not significantly affect the adequacy of basic food in Gorontalo City.